Emotions, confidence, and risk appraisal in athletes with hypermobile joints after anterior cruciate ligament reconstruction: A prospective cohort study - Liaghat, B.; Lindskog, J.; Piussi, R.; Thomeé, R.; Samuelsson, K.; Senorski, E. H. (Scandinavian Journal of Medicine & Science in Sports, 2025)
The objective was to investigate associations between generalized joint hypermobility (GJH) and psychological factors related to return to sport in athletes after anterior cruciate ligament (ACL) reconstruction. In a prospective cohort study using data from a rehabilitation-specific Swedish ACL registry, we included athletes >= 15 years of age following ipsilateral ACL reconstruction with and without GJH using the Beighton score (0-9, 9 = severe hypermobility), with cut points of >= 5/9 for females and >= 4/9 for males. The Anterior Cruciate Ligament-Return to Sport after Injury (ACL-RSI) scale (10-100, 100 = best) was used to assess athletes' emotions, confidence, and risk appraisal 8-24 months post-surgery. We used linear regressions for continuous ACL-RSI scores and logistic regression to compare high (>= 65) vs. low scores to estimate the associations with GJH and Beighton scores, adjusted for age and sex. Data for 1410 athletes (mean age 27.3 years, 56% women, 22% GJH) were extracted from the registry, with soccer (35.8%) and handball (10.4%) being the most common pre-injury sports. At 8-18 months, ACL-RSI scores were associated with both GJH (range of mean beta coefficients -1.16 to -4.27) and Beighton score (range of mean beta coefficients -0.30 to -0.77). At 8 months, athletes with GJH were less likely to exceed the ACL-RSI threshold (odds ratio 0.71; 95% confidence interval 0.53 to 0.96; p = 0.026), with nonsignificant results at 12-24 months for higher Beighton scores. In conclusion, athletes with GJH appear to exhibit lower ACL-RSI scores after ACL reconstruction, compared with athletes without GJH.